Methods of Conducting a Healthy Lifestyle and Health Education in Educational Institutions (Journal of Educational Sciences, 2017)
The article raises the problems and methods of obtaining a competent education in the conduct of a healthy lifestyle of pupils of schools and student youth. Currently, without meeting sanitary and hygienic requirements and observing personal and public hygiene, it is impossible to remain physically healthy. For this, it is necessary to instill in the young people learning the principles of healthy lifestyle, training in basic and additional factors of physical education, contributing to the development of the physical qualities of the younger generation. Recently, the rapid growth of diseases and disabilities among children of senior school age and student youth, not the fulfillment of elementary hygienic standards in the environment, the violation of the regime and the balance of nutrition, the incompetent instructions of negligent «specialists» who do not know the specifics of physical culture, And other negative phenomena that may adversely affect the health of older students and students. And this is fraught with a violation of gender policy, which will adversely affect our country in the future. Therefore, data in the article methods and recommendations can positively influence the younger generation and give other specialists food for thought.Key words: pupils, students, health-improving physical culture, sport, disease prevention, self-education, maintaining a healthy lifestyle.